The Influence of Rewards and Punishments on the Performance of Employees : JEL Classification: L66, M11, M31, O32, Q13 - M. Irfan Maulana Bima; Hasnidar Syam (Journal La Bisecoman, 2026)
This study aims to determine the effect of perceived organizational support and work-life balance on the dimensions of employee engagement, namely vigor, dedication, and absorption among university lecturers in Indonesia. Data were obtained by distributing questionnaires to respondents, namely 170 lecturers working at universities in Java and Sulawesi. The results showed that perceived organizational support had a positive effect on all three dimensions of employee engagement. However, work-life balance only had a positive effect on vigor, while it had no effect on dedication and absorption. Perceived organizational support can be used to improve employee engagement among lecturers in universities.